1970
DOI: 10.1111/j.1399-3054.1970.tb06457.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abscisic Acid, Salicylic Acid and Trans‐cinnamic Acid on Phosphate Uptake, ATP‐level and Oxygen Evolution in Scenedesmus

Abstract: The effects of abscisic acid, salicylic acid and trans‐cinnamic acid were tested on the light‐induced phosphorylating reactions and oxygen evolution of the unicellular green alga Scenedesmus. It was found that abscisic acid and cinnamic acid had practically no influence on the total inorganic phosphate uptake, while salicylic acid in the concentration range of 10‐6 to 10‐3M gave a small decrease in the total inorganic phosphate uptake. The ATP level in the cells is in most cases increased when these three acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Growth was significantly inhibited with the addition of salicylic acid, while the other six allelochemicals were able to inhibit or weakly stimulate the algal growth depending on their concentration (Table 1). Tillberg (1970) found that salicylic acid at concentrations of 10 −6 –10 −3 mol l −1 (0·138–138 mg l −1 ) decreased the phosphorus uptake of the alga Scenedesmus . Meanwhile, Scharff and Perry (1976) reported that under anaerobic conditions, at a low pH and 30°C, yeast lost K + ions in the presence of salicylic acid and glucose utilization was inhibited.…”
Section: Discussionmentioning
confidence: 98%
“…Growth was significantly inhibited with the addition of salicylic acid, while the other six allelochemicals were able to inhibit or weakly stimulate the algal growth depending on their concentration (Table 1). Tillberg (1970) found that salicylic acid at concentrations of 10 −6 –10 −3 mol l −1 (0·138–138 mg l −1 ) decreased the phosphorus uptake of the alga Scenedesmus . Meanwhile, Scharff and Perry (1976) reported that under anaerobic conditions, at a low pH and 30°C, yeast lost K + ions in the presence of salicylic acid and glucose utilization was inhibited.…”
Section: Discussionmentioning
confidence: 98%
“…Abscisic acid is well known to play important roles in the response to various environmental stresses in higher plants. In the case of algae, on the other hand, there have been few reports about its physiological roles (Tillberg 1970; Tietz & Kasprik 1986; Tietz et al . 1989).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few reports about these functions in green algae. With regard to ABA, its physiological roles have been little investigated in algae, although the existence of endogeneous ABA has been confirmed (Tillberg 1970; Tietz & Kasprik 1986; Tietz et al . 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that cellular ATP levels, nitrate uptake and sucrose metabolism are modified by exogenous ABA (Tillberg 1970;Ullrich and Kunz 1984;Salerno 1985). In addition, effects of salt and osmotic stress on production of ABA, and its role in stress tolerance, are well documented.…”
Section: Chlorophytamentioning
confidence: 99%